Antibacterial and rechargeable surface functional nanofiber membrane for healthcare textile application. (26th January 2018) - Yuan, Qinwen; Lu, Zhentan; Zhang, Jiaqi; Chen, Yuanli; Liu, Ke; Wang, Yuedan; Wang, Wenwen; Liu, Qiongzhen; Wang, Dong
Abstract : The membrane could create a clean environment for doctors and patients to prevent nosocomial cross infection and the activity could be recharged. Abstract : Nosocomial cross infection (NCI) seriously threatens human health, causing enormous economic loss. There is a critical need for new healthcare textiles to prevent NCI. Herein, a polymer modified nanoscale porous membrane was prepared by surface graft polymerization. The membrane had excellent antibacterial activity, and the antibacterial activity could be recharged through a simple method. And the membrane had a high filtration rate against bacteria. Excellent antibacterial activity and a high filtration rate mean the membrane could protect users from direct and indirect contact with pathogens, preventing the spread of diseases with the aid of textiles. The successful preparation of an anti-NCI membrane also provides a universal method for exploring nanoscale porous membrane materials as healthcare textiles to block NCI in hospitals.